PARTICLE SIZE EFFECT ON MAGNETIC AND TRANSPORT PROPERTIES OF La0.7Ca0.3MnO3 NANOPARTICLES - Qaseem, S.; Mumtaz, A.; Hasanain, S. K.; Maaz, K. (The Nucleus, 2010)
La0.7Ca0.3MnO3 nanoparticles have been synthesized by modified citrate route with particle sizes of 20, 26 and 32 +3 nm respectively. The structural characterization has been performed by XRD and TEM analyses while magnetic characterization has been performed by vibrating sample magnetometer (VSM). This work presents the study of size effects on magnetic and electrical properties of Ca-doped CMR nanoparticles (La0.7Ca0.3MnO3). Different particle sizes have been prepared by a wet chemical route. Magnetic characterization reveals that magnetization increases with the increase in the particle size and the magnetic transition temperature for larger particles is the same as in the bulk (258K). The ferromagnetic and resistive transitions are however broad compared to the case of bulk presumably due to the role of the surface. The metal-insulator transition temperature is found to be at 158K while the resistivity shows anomalous low temperature behavior with an upturn at low temperatures presu due to coulomb blockade effects. Furthermore, the field dependence of the resistivity displays nonmonotonic behavior and is explained in terms of the field assisted tunneling between grains. PACS: 73.23 Hk; 73.63 –b; 75.47 –m; 75.47 Gk. 75.75 +a